ANTI-MÜLLERIAN HORMONE AND INHIBIN-B LEVEL PROFILE IN CERVICAL CANCER PATIENTS TREATED WITH PACLITAXEL AND CISPLATIN COMBINATION - Abdullah, Nusratuddin; Kouwagam, Anggrainy Dwifitriana; Andina, A. (BALI MEDICAL JOURNAL; Vol 3 No 2 (2014), 2014)
Background: The age of nulliparous women has increased in developed countries and the 5-year  survival rate for the late stage does not exceed 58%. Moreover, as more women are delaying childbearing, preservation of fertility and reproductive function is a major concern when young women are  counseled with regard to the effects of treatment for cervical cancer. Objective : To determine the effect of the combination chemotherapy on serum levels of Anti-Mullerian Hormone (AMH) and inhibin B.  Methods : This study is a prospective cohort study in 16 cervical cancer patients aged 28-48 years who received Paclitaxel-Cisplatin chemotherapy. AMH and inhibin B levels were examined before and after third series chemotherapy. Statistical analysis used the Wilcoxon test with a level of significance selected at 0.05.  Results : There is a significant decrease in median serum levels of AMH and inhibin B patients between before and after Paclitaxel–Cisplatin chemotherapy with p=0.000 (P<0.05). Similarly, a decrease in the median value of serum levels of AMH and inihibin B after Paclitaxel-Cisplatin chemotherapy in each series of chemotherapy was significant with p=0.000 (P<0.05).  Conclusions : Serum levels of AMH and inhibin B in cervical cancer patients who received the combination chemotherapy decreased dramatically after 3 months of chemotherapy and the factors that contribute to the diminution is age.
Keywords: Chemotherapy, Ovarian reserve, AMH, Inhibin B